Perancangan Prototype Aplikasi Pembelajaran Pembuatan Website dengan Metode Human-Centered Design - Gerald Marihot Hasiholan; Ratih Kartika Dewi; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Micro, Small, Medium Enterprises (MSMEs) are businesses run by individuals, households, or small business entities. There was a 56% drop in sales due to the COVID-19 pandemic. This has resulted in MSME actors turning into digital businesses, one of which is the creation of websites with the goal of advertising their products. Previously there have been several learning applications for website creation that can be downloaded, but there are no applications that are easy, free, attractive, and provide freedom for users to choose the final result of the website. Website Development Learning Applications is a solution to be achieved in order to answer the problems that exist. The method that will be used in designing this application is Human-Centered Design (HCD) so that the resulting solution can focus on the user's needs. The final result of this user experience design is a high-fidelity prototype which will then be evaluated using the Usability testing and Heuristic Evaluation method. The results obtained from the Usability Testing evaluation are the user's level of success in using the application and the Heuristic Evaluation method involving three experts who have conducted an evaluation and then found fifteen findings of usability problems. Improvements made will be adjusted according to suggestions from the evaluator.